2015
DOI: 10.1371/journal.pone.0121003
|View full text |Cite
|
Sign up to set email alerts
|

The Invadopodia Scaffold Protein Tks5 Is Required for the Growth of Human Breast Cancer Cells In Vitro and In Vivo

Abstract: The ability of cancer cells to invade underlies metastatic progression. One mechanism by which cancer cells can become invasive is through the formation of structures called invadopodia, which are dynamic, actin-rich membrane protrusions that are sites of focal extracellular matrix degradation. While there is a growing consensus that invadopodia are instrumental in tumor metastasis, less is known about whether they are involved in tumor growth, particularly in vivo. The adaptor protein Tks5 is an obligate comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 33 publications
5
73
1
Order By: Relevance
“…Both integrin β1 and β3 are RGD-binding integrins (Branch et al, 2012) and are important in the regulation of invadopodia maturation (Beaty and Condeelis, 2014;Beaty et al, 2013;Knowles et al, 2013). As integrin β3 is downregulated upon mechanical stimulation, we examined the possibility that this was accompanied by an increase in activity of integrin β1, an integrin subunit known to localize to invadopodia (Mueller et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both integrin β1 and β3 are RGD-binding integrins (Branch et al, 2012) and are important in the regulation of invadopodia maturation (Beaty and Condeelis, 2014;Beaty et al, 2013;Knowles et al, 2013). As integrin β3 is downregulated upon mechanical stimulation, we examined the possibility that this was accompanied by an increase in activity of integrin β1, an integrin subunit known to localize to invadopodia (Mueller et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Invadopodia undergo three distinct phases in their lifetime: initiation, assembly and maturation. The formation of a core structure containing N-WASp (also known as WASL), Tks5 (also known as SH3PXD2A), cofilin and cortactin defines the initiation step (Artym et al, 2006;Blouw et al, 2015;Oser et al, 2009). The assembly phase requires the stabilization of these precursor proteins to continue the actin polymerization needed for maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In rescue experiments, we observed that both the disintegrin domain and metalloproteinase domain of ADAM12 were necessary for rescuing the invadopodia formation defect, and could function in trans to do so. Adhesion rings containing integrins are found at invadopodia and have been shown to be crucial for invadopodia maturation (Branch et al, 2012). Therefore, the disintegrin domain of ADAM12 could potentially regulate adhesion ring dynamics around invadopodia to affect invadopodia formation.…”
Section: Discussionmentioning
confidence: 99%
“…These linear invadosomes are formed along type I collagen fibrils and are found in both normal and transformed cells (Di Martino et al, 2015;Juin et al, 2012;Juin et al, 2014;Schachtner et al, 2013). Linear invadosomes present markers that are common to all invadosomes, such as the actin-binding proteins N-WASP and cortactin (Artym et al, 2006), the scaffold protein tyrosine kinase substrate 5 (Tks5, also known as SH3PXD2A) (Blouw et al, 2015) and the Rho GTPase Cdc42 (Di . Linear invadosomes, in contrast to invadosomes that are organised into individual dots, do not contain ring proteins, such as talin, vinculin, paxillin or integrins (Juin et al, 2012).…”
Section: Induction Of Invadosome Formationmentioning
confidence: 99%